2019
DOI: 10.1080/24748668.2019.1615296
|View full text |Cite
|
Sign up to set email alerts
|

Probability of winning and match length in Tiebreak Ten tennis

Abstract: New formats of tennis have been developed to make matches more exciting and unpredictable than the traditional format of the game. The purpose of the current investigation was to compare and the probability of winning between Tiebreak Ten matches and two other formats of the game; Fast4 tennis and traditional tennis. A probabilistic model of winning Tiebreak Ten tennis matches was created and compared with existing models of Fast4 and traditional tennis matches. This analysis was done for a full range of proba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
1
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
(31 reference statements)
2
1
0
1
Order By: Relevance
“…Given that Simpson's Paradox is less of an issue in Thirty30 tennis than in traditional tennis, the primary explanation for the greater number of upsets in Thirty30 tennis is due to the games being shorter and hence less representative of player ability. This is consistent with research into other shorter formats of tennis which has found that they also have a higher chance of upsets than traditional tennis (Simmonds and O'Donoghue, 2018;O'Donoghue and Simmonds, 2019). This knowledge may be useful to tournament organisers who need to decide on game formats.…”
Section: Discussionsupporting
confidence: 85%
“…Given that Simpson's Paradox is less of an issue in Thirty30 tennis than in traditional tennis, the primary explanation for the greater number of upsets in Thirty30 tennis is due to the games being shorter and hence less representative of player ability. This is consistent with research into other shorter formats of tennis which has found that they also have a higher chance of upsets than traditional tennis (Simmonds and O'Donoghue, 2018;O'Donoghue and Simmonds, 2019). This knowledge may be useful to tournament organisers who need to decide on game formats.…”
Section: Discussionsupporting
confidence: 85%
“…Compared with the traditional techniques and tactics analysis methods, the data mining technology can more clearly describe and analyse the stroke position and route, the process, and the sequence of losing points [12,13]. It can help the coach better grasp the general character and characteristics of players' techniques and tactics and provide reference and basis for the training and application of techniques and tactics in the future [14,15]. e rest of this paper is organized as follows: Section 2 discusses the present situation of research on the technique and tactics of Chinese Women Tennis players, followed by the methods in Section 3. e experiment is discussed in Section 4.…”
Section: Introductionmentioning
confidence: 99%
“…We confirmed that two studies used data mining theory (O'Donoghue and Simmonds, 2019;Li et al, 2021). As mentioned below, there were many studies that used published data on the Internet.…”
Section: Discussion 1) Studies Using Primary Data Collectionsupporting
confidence: 80%